2015
DOI: 10.1186/s12891-015-0611-5
|View full text |Cite
|
Sign up to set email alerts
|

The extent and risk of knee injuries in children aged 9–14 with Generalised Joint Hypermobility and knee joint hypermobility - the CHAMPS-study Denmark

Abstract: BackgroundGeneralised Joint Hypermobility (GJH) is suggested as an aetiological factor for knee injuries in adolescents and adults. It is presumed that GJH causes decreased joint stability, thereby increasing the risk of knee injuries during challenging situations like jumping and landing. The aim was to study the extent and risk of knee injuries in children with GJH and knee hypermobility.MethodsIn total, 999 children (9–14 years) were tested twice during spring 2012 and 2013 with Beighton´s Tests (BT) for hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
3
12
1
1
Order By: Relevance
“…2,30,39 The current study did not find increased self-reported injury frequency in elite-level adolescent athletes with GJH, which is consistent with the results of a recent study on children. 19 However, this is in contrast to the results of a previous systematic review, in which GJH was associated with an increased risk of knee injuries in athletes from a wide age range (9-39 years old) who participated in different sports, especially contact sports. 33 Our results also contrast with those of a 5-year follow-up study, in which more adult dancers with GJH had multiple joint pain and had to take time off from dancing (greater than 6 weeks) due to injury.…”
contrasting
confidence: 55%
“…2,30,39 The current study did not find increased self-reported injury frequency in elite-level adolescent athletes with GJH, which is consistent with the results of a recent study on children. 19 However, this is in contrast to the results of a previous systematic review, in which GJH was associated with an increased risk of knee injuries in athletes from a wide age range (9-39 years old) who participated in different sports, especially contact sports. 33 Our results also contrast with those of a 5-year follow-up study, in which more adult dancers with GJH had multiple joint pain and had to take time off from dancing (greater than 6 weeks) due to injury.…”
contrasting
confidence: 55%
“…The current study is in line with previous studies showing the prevalence of GJH increasing by age for girls and decreasing by age for boys [ 8 , 23 , 24 ]. Thus, the choice of cut off points for classification of GJH may vary from ≥4/9 to ≥6/9 within this age group [ 8 , 11 , 12 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is recognised as a relatively high prevalence compared with a normal child population (mean age 13.8 years), where only 7 % of the girls were classified GJH at this cut off point [ 25 ]. It seems difficult to determine a single cut off point for children and adolescents, since joint mobility represents a variable fluctuating condition during maturation [ 24 ]. It is therefore recommended that future studies present data of GJH prevalence with different cut off points, in addition to age and gender, as presented in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The validity for BS and the association with pain showed moderate positive to conflicting evidence in five studies (all on children) [El‐Metwally et al, , , , Tobias et al, ; Sohrbeck‐Nøhr et al, ]. For the validity of BS and the association with injuries the validity showed conflicting evidence in three studies (one in children) [Roussel et al, ; Cameron et al, ; Junge et al, ]. For the validity of BS and the association with different diseases (Temporo‐Mandibular Disorders, Chronic Fatigue Syndrome, Adhesive Capsulitis) there was limited positive to conflicting evidence in three studies [Nijs et al, ; Hirsch et al, ; Terzi et al, ].…”
Section: Resultsmentioning
confidence: 99%